Permasalahan dan Solusi Pendidikan di Daerah Kepulauan: Studi Kasus di SMA Negeri 1 Pulau Aceh, Kabupaten Aceh Besar - M. Adlim; Helida Gusti; Zulfadli Zulfadli (Jurnal Pencerahan, 2016)
Educational problematic and the alternative solutions of Senior High School in rural-isolated-small Island have been studied. The subject school was located in small village in Pulau Nasi Island, about one hour sailing by small boat from the state capital, Banda Aceh, Indonesia. Data were collected based on structured interviews, questioners, direct observation and focus group discussion (FGD). The respondents were the school principal, teachers, students and representative community people as well as the Head of District Education Office. This study found that the subject school has C grade according to national education standard parameters and it has the lowest national examination score among senior high schools in the district. The majority of teachers (60%) do not stay on the isolated island and it caused the curriculum was not accomplished. Majority respondents said very often teachers were not in the classroom because they could not come to the island due to bad weather (high wave ocean) and other reasons. They came to the school only at their teaching hours and then back to the mainland so that their interaction time with the students was very limited. The characteristics of teachers who stay on the island are those who married or have relative with the local resident and temporary contracted teachers who are proposing to be hired as government permanent teachers. Majority teachers who already hold permanent job status stay on the mainland (city) and they prefer to take risk sailing to the island weekly rather than staying in the village. These phenomena do not occur in the bigger island (Simeulue) where is a district capital with town facilities. To overcome this problem, the majority respondents suggested several alternative solutions including improvement in the school management such as hiring new contracted teachers to replace current teachers who are not willing stay on the small island. The district education was also insisted to implement education regulation consistently